Current Problems of the Integration of Graduates in Germany and Japan (Malaysian Management Journal, 1997)
The continuing economic crisis in most of the developed countries makes it necessary to discuss the reasons for the very high unemployment rates in many countries, especially the current problems of the integration of graduates in Germany and Japan. In the case of Japan, the hiring situation of graduates for 1 994 and 1 995 promised to be the most dire in memory and therefore Japan's labour market problems are comparable to that of Germany. The governments and the labour market administrations in Germany and Japan have to strengthen their efforts to integrate most of their young graduates, and the universities on their part, have to qualify their students in a professionally-oriented way. Those companies which cease hiring graduates are bound to lose in a mid-term view.